1991
DOI: 10.1002/jcb.240450212
|View full text |Cite
|
Sign up to set email alerts
|

Taurine release associated to volume regulation in rabbit lymphocytes

Abstract: Rabbit lymphocytes exposed to hyposmotic media first swell and then recover their initial volume within 6 min. During volume recovery, free amino acids (FAA) decrease from 451.1 to 208 nmoles/mg protein. Taurine was the dominating FAA, accounting for 70% of the FAA pool. The time course of 3H-taurine release induced by hyposmolarity followed that of volume recovery. Efflux of 3H-taurine in an 8 min period was 17.8% (of total labeled taurine accumulated during loading) in an isosmotic medium. Reducing osmolarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Exclusion of Cl -contributes to RVD responses. Regulatory volume increase (RVI) is mediated by transport of Na + and Cl -through cotransporter and exchanger [10][11][12]. Results obtained in this study indicate that DPC-sensitive transport of Cl -, but not Na + , is related to the vacuole formation in the cells with the hypotonic stress.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Exclusion of Cl -contributes to RVD responses. Regulatory volume increase (RVI) is mediated by transport of Na + and Cl -through cotransporter and exchanger [10][11][12]. Results obtained in this study indicate that DPC-sensitive transport of Cl -, but not Na + , is related to the vacuole formation in the cells with the hypotonic stress.…”
Section: Discussionmentioning
confidence: 55%
“…RVD is mediated by the rapid extrusion of osmolytes such as K + , Cl -and amino acid through ion channels, exchangers and cotransporters [6,[10][11][12]32]. Blockers for Cl -channels inhibit the chloride efflux, taurine efflux and RVD response [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osmotic swelling of human lung epithelial cancer (Sl) cells was shown here to result in the activation of a pathway which mediated the ehlux of the non-essential sulfonic amino acid, taurine. In this respect Sl cells resemble a wide variety of other mammalian cell-types including epithelial [ 17,181, brain [20,22,24] and blood [19] cells, as well as numerous lower vertebrate and marine invertebrate cells (reviewed by Chamberlin and Strange [42]). In Sl cells swollen in a low K' saline the volume-activated efflux component declined steadily with time so that within 40-80 min the flux in the hypo-osmotic solution had reverted to the basal level measured under iso-osmotic conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In vertebrate cells the primary organic 'osmolyte' is usually tam-me, a sulfonic amino acid which may be present in the cytoplasm at concentrations of up to 40 mM [3]. Volume-activated taurine release has been demonstrated from many vertebrate cells and tissues including fish erythrocytes, heart, brain and hepatocytes [4-121, bird erythrocytes [13], Ehrlich ascites tumour cells MDCK cells [17,18], rabbit lymphocytes [19], and a variety of mammalian brain cell-types . These studies have revealed a number of common characteristics for the transport mechanisms which mediate volume-activated taurine release from different cells: they are, in general, Na'-independent, non-saturable and not prone to 'trans-stimulation' [6,1.5,18,22,25].…”
Section: Introductionmentioning
confidence: 99%